Breast-feeding and the Working Mother in Nairobi - Lakati, Alice; Binns, Colin; Stevenson, Mark (Public Health Nutrition, 2002)
Objective: In the fast growing city of Nairobi, women often combine the roles of mother and worker in trying to achieve better standards of living. The objective of this study was to document the effect of returning to work on breast-feeding by mothers in Kenya. Design: A cross-sectional survey. Setting: Outpatient clinics of two major hospitals in Nairobi, one government hospital in an economically deprived area and one high-fee private hospital. Subjects: Four hundred and forty-four working mothers from low and higher socioeconomic areas in Nairobi. All working mothers with infants aged 4 to 12 months attending during the survey period were invited to participate. Results: The prevalence of breast-feeding at the time of interview was found to be 94.1%. The lower socio-economic group exhibited a higher prevalence of breastfeeding (99%), 10% greater than the higher socio-economic group. The mean number of hours the mothers were away from home due to work was 46.2 hours each week. The majority (54.4%) of the mothers employed a ‘house-girl’ to care for their infant while they were at work, while 28.4% were able to take their infants to work. Most of the breast-feeding mothers (95%) breast-fed their infants at least three times a day and only 23 mothers reported not being able to breast-feed their infants during the day. The lower socio-economic group had a mean of 5.09 breast-feeding times per day while the higher socio-economic group had a mean of 3 times a day. In a logistic regression analysis the mode of work (fixed working hours vs. shift working hours) was associated with exclusive breast-feeding at one month (odds ratio (OR) ¼ 0.45) and two months (OR ¼ 0.39). Conclusion: In Western countries ‘return to work’ is often cited as the reason that breast-feeding is discontinued prematurely. In this study we have shown how mothers in Kenya are able to successfully continue breast-feeding after they have returned to work, often for very long hours.
Keywords: Nairobi; Kenya; Breast-feeding; Working mothers